Investigation of dielectric constants of water in a nano-confined pore. Issue 15 (27th February 2020) - Zhu, Haochen; Yang, Fengrui; Zhu, Yunjie; Li, Aihua; He, Wenzhi; Huang, Juwen; Li, Guangming
Abstract : Investigation of dielectric properties in a silica hydrophilic pore with two water reservoirs. Abstract : We report the dielectric properties of pure water confined in a silica hydrophilic nanopore determined from the computation of the density of liquid in the confined phase by the grand canonical Monte Carlo (GCMC) simulations. The silica cylindrical nanopore is divided into n concentric radial shells to get a better insight into the dielectric properties of nanoconfined water. We find that the average values of the dielectric constants are very close and almost independent of the number of concentric radial shells. The decrease in the dielectric constant of confined pure water is due to the strong orientation of water dipoles in the vicinity of the surface while water dipoles do not exhibit any preferential orientation in bulk phase.